2008
DOI: 10.1080/02699050802336989
|View full text |Cite
|
Sign up to set email alerts
|

Changes of cognitive functioning following mild traumatic brain injury over a 3-month period

Abstract: Findings suggest that attention dysfunction is noticeable immediately following a mild TBI. Different attention functions appear to recover at a different pace over time, suggesting that the condition may have a differential impact on the different sub-types of attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 34 publications
4
43
0
Order By: Relevance
“…Most studies have suggested that cognitive deficits occur shortly after injury with the impairment usually dissipating at 1-3 months post injury (Belanger, Curtiss, Demery, Lebowitz, & Vanderploeg, 2005;Dikmen, McLean, & Temkin, 1986;Frencham, Fox, & Maybery, 2005;Levin et al, 1987b;Ponsford et al, 2000;Rohling et al, 2011;Schretlen & Shapiro, 2003). Still other, often smaller, studies have shown that persistent impairment can be present in patients with mild TBI (Barth et al, 1983;Bernstein, 2002;Kwok, Lee, Leung, & Poon, 2008;Leininger, Gramling, Farrell, Kreutzer, & Peck, 1990;Ruff et al, 1994;. Impairments in a range of cognitive domains at long-term follow up have been documented after mild TBI, (Konrad et al, 2010) with most deficits involving attention and concentration Kwok et al, 2008;Ruff et al, 1994), memory, (Barth et al, 1983;Bernstein, 2002;Dikmen et al, 1986;Frencham et al, 2005;Leininger et al, 1990) speed of information processing , verbal fluency (Kwok et al, 2008), and executive functions Levin et al, 1987b).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most studies have suggested that cognitive deficits occur shortly after injury with the impairment usually dissipating at 1-3 months post injury (Belanger, Curtiss, Demery, Lebowitz, & Vanderploeg, 2005;Dikmen, McLean, & Temkin, 1986;Frencham, Fox, & Maybery, 2005;Levin et al, 1987b;Ponsford et al, 2000;Rohling et al, 2011;Schretlen & Shapiro, 2003). Still other, often smaller, studies have shown that persistent impairment can be present in patients with mild TBI (Barth et al, 1983;Bernstein, 2002;Kwok, Lee, Leung, & Poon, 2008;Leininger, Gramling, Farrell, Kreutzer, & Peck, 1990;Ruff et al, 1994;. Impairments in a range of cognitive domains at long-term follow up have been documented after mild TBI, (Konrad et al, 2010) with most deficits involving attention and concentration Kwok et al, 2008;Ruff et al, 1994), memory, (Barth et al, 1983;Bernstein, 2002;Dikmen et al, 1986;Frencham et al, 2005;Leininger et al, 1990) speed of information processing , verbal fluency (Kwok et al, 2008), and executive functions Levin et al, 1987b).…”
Section: Introductionmentioning
confidence: 96%
“…Still other, often smaller, studies have shown that persistent impairment can be present in patients with mild TBI (Barth et al, 1983;Bernstein, 2002;Kwok, Lee, Leung, & Poon, 2008;Leininger, Gramling, Farrell, Kreutzer, & Peck, 1990;Ruff et al, 1994;. Impairments in a range of cognitive domains at long-term follow up have been documented after mild TBI, (Konrad et al, 2010) with most deficits involving attention and concentration Kwok et al, 2008;Ruff et al, 1994), memory, (Barth et al, 1983;Bernstein, 2002;Dikmen et al, 1986;Frencham et al, 2005;Leininger et al, 1990) speed of information processing , verbal fluency (Kwok et al, 2008), and executive functions Levin et al, 1987b). In particular executive functions are considered higher order regulatory functions that rely on the integrity of frontal but also temporal and parietal areas (Duncan, 2013;Stuss, 2011;Vincent, Kahn, Snyder, Raichle, & Buckner, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Paré et al showed patients with mild TBI to have auditory working memory deficits as demonstrated by poorer digit span performance than nondisabled controls immediately after their injury and at 3-month follow-up [25]. Kwok et al reported that patients with a mild TBI performed more poorly than nondisabled controls immediately after injury and at 1-month followup on neuropsychological tests that included measures of both auditory and visual information processing (i.e., divided attention assessed with the Symbol Digit Modalities Test, sustained attention assessed with the Digit Vigilance Test, verbal recognition assessed with the Chinese Auditory Verbal Learning Test, and verbal fluency assessed with the Verbal Fluency Test) [26]. These individuals also had poorer sustained attention immediately after injury and at 1-and 3-month follow-ups.…”
Section: Methodsmentioning
confidence: 99%
“…However, some exhibit persisting difficulties beyond 3 months after injury (e.g. Alexander, 1995;Kwok et al, 2008;Leininger et al, 1990). A further selection criterion was therefore a post-injury interval of 3 months or longer to ensure that any change in communication associated with the injury would have stabilised and become part of the person's communicative repertoire.…”
Section: Selection and Description Of The Individuals With Mtbimentioning
confidence: 99%
“…Neuropsychological sequelae of MTBI have been found to include difficulties with reasoning, information processing, verbal memory and attention to detail, as well as slowed reaction time and reduced error recognition (Kwok, Lee, Leung & Poon, 2008; Leininger, Gramling, Farrell, Kreutzer & Peck, 1990;Voller et al, 1999). The frontal lobes of the brain are vulnerable to injury in TBI (McDonald, Flashman & Saykin, 2002).…”
mentioning
confidence: 99%